2015
DOI: 10.3390/molecules20021984
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Applications of Covalent Docking in Drug Discovery: Merits and Pitfalls

Abstract: The present art of drug discovery and design of new drugs is based on suicidal irreversible inhibitors. Covalent inhibition is the strategy that is used to achieve irreversible inhibition. Irreversible inhibitors interact with their targets in a time-dependent fashion, and the reaction proceeds to completion rather than to equilibrium. Covalent inhibitors possessed some significant advantages over non-covalent inhibitors such as covalent warheads can target rare, non-conserved residue of a particular target pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 66 publications
(69 reference statements)
1
88
0
2
Order By: Relevance
“…Although the antibacterial potential of P.ferulacea and P.uloptera has been demonstrated in several studies but the antibacterial mechanisms of the active constituents of these plants have not well defined. Molecular docking is one of best bioinformatic tools for drug design and determination the mechanism of antimicrobial agents (Kumalo et al, 2015).In the present study, the docking between 10 known compounds from P.ferulacea and bacterial proteins has been done.The results showed that the antibacterial activity of pinens of this plant was significantly more than coumarins. DNAgyrase subunit B was the main target proteins of pinens.The α-pinen was more effective than β-pinen with lowest and highest Ki and ∆Gb values respectively.Pinens ( were the main target proteins of tested coumarins.Among the tested coumarins,osethole was most effective which followed by Pesoralen,Isoimpratorin, Terpinolen,Gosferol, δ-3-caren, P-cymene, and Myrcene respectively.Coumarins are secondary metabolites that occur naturally in several plant families and possess important pharmacological properties, including inhibition of oxidative stress and use as the fragrance in food and cosmetic products (Borges et al, 2014).The antibacterial activity of some coumarins such as osthol,imperatorin, isoimpinellin.arbutin,baicalin and naringin have been reported previously (Widelski et al, 2009;Ng et al, 1996).The mechanisms of antibacterial effect of these compounds have not well defined and the present study is the first investigation of the mechanism of antibacterial activity of coumarins and pinens.Despite the therapeutic advantages possessed by medicinal plants but some constituents of medicinal plants have been shown to be potentially mutagenic,toxic, teratogenic and carcinogenic (Gadano et al, 2006;Akinboro and Bakare, 2007).Therefore, these plants should be evaluated to better understand their safety.The Ames test is commonly used with plant extracts for possible gene mutation determination (Mortelmans et al, 2000).In this study the Ames test was carried out using methanolic extracts of flower, leaf, stem, root and seeds from P.ferulacea and P.uloptera obtained results have not shown any mutagenicity to TA98 for both studied plants.…”
Section: Insilico Analysis Of Antimicrobial Activitymentioning
confidence: 99%
“…Although the antibacterial potential of P.ferulacea and P.uloptera has been demonstrated in several studies but the antibacterial mechanisms of the active constituents of these plants have not well defined. Molecular docking is one of best bioinformatic tools for drug design and determination the mechanism of antimicrobial agents (Kumalo et al, 2015).In the present study, the docking between 10 known compounds from P.ferulacea and bacterial proteins has been done.The results showed that the antibacterial activity of pinens of this plant was significantly more than coumarins. DNAgyrase subunit B was the main target proteins of pinens.The α-pinen was more effective than β-pinen with lowest and highest Ki and ∆Gb values respectively.Pinens ( were the main target proteins of tested coumarins.Among the tested coumarins,osethole was most effective which followed by Pesoralen,Isoimpratorin, Terpinolen,Gosferol, δ-3-caren, P-cymene, and Myrcene respectively.Coumarins are secondary metabolites that occur naturally in several plant families and possess important pharmacological properties, including inhibition of oxidative stress and use as the fragrance in food and cosmetic products (Borges et al, 2014).The antibacterial activity of some coumarins such as osthol,imperatorin, isoimpinellin.arbutin,baicalin and naringin have been reported previously (Widelski et al, 2009;Ng et al, 1996).The mechanisms of antibacterial effect of these compounds have not well defined and the present study is the first investigation of the mechanism of antibacterial activity of coumarins and pinens.Despite the therapeutic advantages possessed by medicinal plants but some constituents of medicinal plants have been shown to be potentially mutagenic,toxic, teratogenic and carcinogenic (Gadano et al, 2006;Akinboro and Bakare, 2007).Therefore, these plants should be evaluated to better understand their safety.The Ames test is commonly used with plant extracts for possible gene mutation determination (Mortelmans et al, 2000).In this study the Ames test was carried out using methanolic extracts of flower, leaf, stem, root and seeds from P.ferulacea and P.uloptera obtained results have not shown any mutagenicity to TA98 for both studied plants.…”
Section: Insilico Analysis Of Antimicrobial Activitymentioning
confidence: 99%
“…Recent reports have claimed that approximately one-third of the currently marketed enzyme modulators are covalent inhibitors [88]. Covalent ligands act by irreversibly inactivating their targets; consequently, recovery of the inhibited biological function involves re-synthesis of the targeted protein.…”
Section: Covalent Bonds In Molecular Dockingmentioning
confidence: 99%
“…Molecular docking is the computational method for structure-based drug designing which gives an idea about the proper and stable conformation of ligand and target protein and also tells about suitable protein ligand interactions [41].Binding energy is nothing but the binding strength of the ligand which not only help predicting the stable conformation of ligand-protein complex but also optimize the newly formed bonds [42].Docking result based on their binding energies is shown in the Table 1. Analysis of docking results shows binding energies in a range of -4.48 Kcal/mol to -7.25kcal/mol.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Promising binding poses of all theses enzymes are shown in Figure1b and Figure 3. The non-covalent interactions are conventional methods and are proven to be effective in prediction of different binding modes of protein ligand complexes [41]. Non-covalent interactions include hydrophobic interactions, hydrogen bonding, van der waals interaction and the electrostatics interaction [43].…”
Section: Molecular Docking Analysismentioning
confidence: 99%